Exploring the Needs and Challenges of Adults from War Affected Backgrounds - Karen Magro (Adult Education Research Conference, 2007)
This research explores the literacy challenges of adults from war-affected countries, and highlights the changing role of literacy educators working with adults escaping war zones. Strategies designed to reduce learning barriers as well as an analysis of the social, cultural, and emotional dimensions of literacy learning will be explored.